Are Clinical Guidelines for the Management of Intraductal Papillary Mucinous Neoplasms Followed?: A Single-Center Analysis. Issue 2 (February 2017) - Tabrizian, Parissa; Berger, Yaniv; Pierobon, Elisa Sefora; Aycart, Samantha; Argiriadi, Pamela; Fei, Kezhen; Carrasco-Avino, Gonzalo; Labow, Daniel M.; Sarpel, Umut
Abstract : Objectives: This study aimed to determine how frequently guidelines for the management of intraductal papillary mucinous neoplasms (IPMNs) are followed and establish factors associated with failure. Methods: Four hundred forty-five patients with radiographic diagnosis of IPMN 1 cm or greater between January 1, 2003 and January 1, 2013 were included. We defined failure of guideline adherence if the following occurred: ( a ) failure of acknowledgment of IPMN, ( b ) failure to undergo endoscopic ultrasound, ( c ) failure to undergo resection, or ( d ) failure to undergo at least 1 surveillance image within 2 years after diagnosis. Results: Failure of guideline adherence was observed in 58% of patients and evident across all the respective criteria (A: 38%, B: 25%, C: 29%, D: 33%). Age older than 68 years ( P < 0.01), American Society of Anesthesiologists score of 3 or higher ( P < 0.0001), benign findings on imaging ( P < 0.0001), and major comorbid conditions ( P < 0.01) were factors associated with higher rate of failure to compliance. On multivariate logistic regression, American Society of Anesthesiologists score of 3 or higher and benign features were associated with 4.0 times (95% confidence interval, 2.02–8.06) and 2.6 times (95% confidence interval, 1.60–4.07) higher odds of failure to compliance with guidelines, respectively. Conclusions: Compliance with clinical guidelines for the management of IPMN is poor. Socioeconomic factors do not seem to create a disparity to care. However, many patients with IPMN have other medical diagnoses that take priority over IPMN surveillance and treatment.